The novel estrogen receptor GPER1 decreases epilepsy severity and susceptivity in the hippocampus after status epilepticus. (29th May 2020) - Zuo, Di; Wang, Feng; Rong, Weifang; Wen, Yujun; Sun, Kuisheng; Zhao, Xiaopeng; Ren, Xiaofan; He, Zhenquan; Ding, Na; Ma, Lin; Xu, Fang
Highlights: GPER1 played a protective role by reducing seizure severity and susceptivity in a rat model of pilocarpine-induced SE. Changes in inflammation paralleled the changes in GPER1-regulated seizure activity. Abstract: The steroid hormone 17β-estradiol (estrogen) exerts neuroprotective effects in several types of neurological disorders including epilepsy. The novel G protein-coupled estrogen receptor 1 (GPER1), also called GPR30, mediates the non-genomic effects of 17β-estradiol. However, the specific role of GPER1 in status epilepticus (SE) remains unclear. In this report, we evaluated the effects of GPER1 on the hippocampus during SE and the underlying mechanism was studied. Our results revealed that pilocarpine-induced GPER1-KD epileptic rats exhibited a shorter latency to generalized convulsions and strikingly elevated seizure severity. Additionally, the electroencephalographic seizure activity also corresponded to these results. Fast-Fourier analysis indicated an enhancement of power in the theta and alpha bands during SE in GPER1-KD rats. In addition, epilepsy-induced pathological changes were dramatically exacerbated in GPER1-KD rats, including neuron damage and neuroinflammation in hippocampus. GPER1 might be associated with the susceptibility to and severity of epileptic seizures. In summary, our results suggested that GPER1 plays a neuroprotective role in SE, and might be a candidate target for epilepsy therapy.